PERANCANGAN KOMIK INSTAGRAM TENTANG KEPRIBADIAN INTROVERT - Azhari Almirana; Shienny Megawati (Jurnal Vicidi, 2021)
ABSTRACT Every human being is born with various types of characteristics that are different from one another. To find out the type of characteristics in humans, experts from ancient times until now have continued to study this topic, for example by taking an individual approach such as conducting a personality test. One of the personality traits that are well known to both the general public and psychologists is the introvert and extrovert personality. However, the representation of characters with introverted personalities in the media is still not displayed properly, creating negative stereotypes and misconceptions in society, including in Indonesia. With the rapid development of technology, such as the existence of social media platforms, it makes it easy to share information quickly and easily. Making digital comics on Instagram as a communication medium can be effective because the younger generation prefers visual content. The sources reviewed in this literature study use reliable, registered, and have a DOI / ISBN source. Most of the sources of scientific articles and books that have been published in the last 5-10 years. Keywords: Personality, Introvert, Representation, Comic, Social Media, Indonesia